Abitare liminale permanente. Pratiche di lotta e negoziazione quotidiana degli spazi in un’occupazione abitativa romana - Cacciotti, Chiara (Antropologia Pubblica, 2024)
The article explores the notion of stretched and permanent liminality by foregrounding the ways in which people living in a Roman organized squat deal with it in their everyday lives. It focuses on the case of Santa Croce/Spin Time, a squat occupied by the Housing rights movement Action in 2013 characterized by both a residential and a socio-cultural part. Relying on extensive ethnographic observations and interviews undertaken within the building, the article mobilizes and grounds in the field the Turnerian notion of communitas as anything but a short-term and temporary condition. By describing inhabitants and activists as capable of finding creative ways to negotiate their domestic and common spaces and elaborating on new political instruments to deal with their liminal condition, the article contributes to debates around liminal homing practices in conditions of alleged uninhabitability.